(untitled) (Italian Review of Legal History, 2015)
The studies of the Belle Époque on matters of company law reached, in Italy, a very high technical and cultural level, despite the tardiness in the capitalistic and industrial development and undoubtedly deserve in-depth investigation. In fact, they benefitted from a time, so to speak, both from the general climate of renewal of legal studies in a liberal State grappling with the many social and financial problems of economic development, and from the special circumstances of those years, marked by the widest circulation of people, ideas and capital beyond the national state borders.